THE BLOOD CREATININE LEVELS OF HYPERTENSIVE PATIENTS OF PRODUCTIVE AGE AT THE CIKAJANG COMMUNITY HEALTH CENTER - Rismawati, Rismawati; Mutmaina, Gina Nafsa; Sugiah, Sugiah; Nurisani, Astari; Arbila, Meisya (Karsa Husada Health Institute Garut, 2024)
The incidence of hypertension is on the rise with the passage of time, attributed to the increasing prevalence of unhealthy lifestyle changes. The productive age signifies a stage in the evolution of life where individuals are at the peak of activity, characterized by heightened levels of engagement that tend to result in health issues. Hypertension can lead to organ damage, notably the kidneys, as indicated by elevated levels of creatinine in the blood. The aim of this study is to ascertain the levels of blood creatinine in hypertensive patients of productive age at the Cikajang Community Health Center. This descriptive study analyzes blood creatinine levels in hypertensive patients using the Jaffe Reaction method, with a sample size of 30 respondents obtained through accidental sampling technique. The study's findings reveal that 19 participants (64%) have normal creatinine levels, 10 participants (33%) have high creatinine levels, and 1 participant (3%) has low creatinine levels. The study concludes that the majority of respondents have normal creatinine levels, nearly half of the respondents have high creatinine levels, and a small portion of respondents have low creatinine levels